Apple Peel Supplementation Potential in Metabolic Syndrome Prevention - Joanna Popiolek-Kalisz; Paweł Glibowski (Life, 2023)
(1) Introduction: Apples are a source of bioactive substances, e.g., anthocyanidins and flavonols, and dietary fiber. Their highest concentrations are observed in the skin. Metabolic syndrome (MetS) is a set of conditions originally associated with obesity. Excessive adipose tissue accompanying obesity leads to chronic inflammation and metabolic disorders, which result in the development of dyslipidemia, elevated blood pressure, and glucose levels. Thus, supplementation of apple peels, a source of antioxidant substances and fiber, could potentially be a method supporting the prevention of MetS. This paper summarizes the results of available research on the potential impact of apple peel supplementation on the components of MetS. (2) Results: The results from in vitro and animal model studies indicate a positive effect of apple peel supplementation on lipid profile, glucose levels, and blood pressure regulation mediators. Only one human study was performed, and it showed that the consumption of apple peels had an effect on endothelial function but not on other clinical parameters. At the moment, there are no results from observations on large groups of people available. (3) Conclusions: The results of in vitro and animal-model studies indicate the potential of apple peel supplementation in MetS prevention, but it has not been clinically confirmed in human studies. Conducting large human studies could allow a definite clarification of the role of apple peel supplementation in MetS prevention.